The atomic lensing model: new opportunities for atom-by-atom metrology of heterogeneous nanomaterials - Van Den Bos, K; Janssens, L; De Backer, A; Nellist, P; Van Aert, S (Elsevier, 2018)
The atomic lensing model has been proposed as a promising method facilitating atom-counting in heterogeneous nanocrystals [1]. Here, image simulations will validate the model, which describes dynamical diffraction as a superposition of individual atoms focussing the incident electrons. It will be demonstrated that the model is reliable in the annular dark field regime for crystals having columns containing dozens of atoms. By using the principles of statistical detection theory, it will be shown that this model gives new opportunities for detecting compositional differences.